Pengaruh Sistem Pajak, Sanksi Pajak, dan Keadilan Pajak terhadap Penggelapan Pajak : (Studi Kasus pada KPP Pratama Bekasi Utara) - Ahmad Ali; Cris Kuntadi; Maidani Maidani (Universitas 45 Surabaya, 2024)
This study was conducted to examine the effect of the taxation system, tax sanctions, and tax justice on tax evasion. Data collection was carried out using a questionnaire. The sample in this study were taxpayers registered at KPP Pratama Bekasi Utara, with a sample size of 100 taxpayers. The data analysis used is the method with the help of the SPSS 26 program. The results showed that justice and the tax system affect tax evasion. the tax system affects tax evasion. tax justice affects tax evasion.